DEVELOPMENT OF PROJECT BASED LEARNING CENTER INSTRUCTIONAL PACKAGE: A CASE STUDY OF SMART HOME SYSTEM - Khunchai, Seree; Thongchaisuratkrul, Chaiyapon (Journal of Education and Innovation, 2023)
This research aimed to 1) develop a project-based learning center instructional package: a case study of smart home system, 2) to determine the effectiveness of the instructional package, 3) compare the learning achievements between before learning and after learning, 4) assess the work skills and project skills of learners studying with the instructional package, and 5) to study the satisfaction of the learners who study with the developed project-based learning center instructional package. The development of this instructional package surveyed the needs of 20 people involved in education and establishments and conducted a try-out with 220 students, pupils and other interested individuals. There are 5 experts assessing the quality of the instructional package. After revising, then using with a sample group of 30 students by a specific method. The results were as follows: 1) the analysis found that the quality of the instructional package by experts had the highest level ( = 4.79, SD = 0.45), 2) the project-based learning center instructional package, Smart Home Case Studies, has an efficiency E1/E2 of 76.87/80. 73 according to the specified criteria, 3) learning through the instructional package developed gave learners a statistically significantly higher level of knowledge at .05, 4) Participants passed an average of 81.50% of all operational skills assessments and an average of 84.00% of project skills, and 5) the overall satisfaction of the learners towards the instructional package was at a high level including a large scale Value ( = 4.28, SD = 0.74).